A single systemic inflammatory insult causes acute motor deficits and accelerates disease progression in a mouse model of human tauopathy. Issue 1 (1st January 2019) - Torvell, Megan; Hampton, David W.; Connick, Peter; MacLullich, Alasdair M.J.; Cunningham, Colm; Chandran, Siddharthan
Abstract: Introduction: Neuroinflammation, which contributes to neurodegeneration, is a consistent hallmark of dementia. Emerging evidence suggests that systemic inflammation also contributes to disease progression. Methods: The ability of systemically administered lipopolysaccharide (LPS ‐ 500 μg/kg) to effect acute and chronic behavioural changes in C57BL/6 and P301S tauopathy mice was assessed. Markers of pathology were assessed in the brain and spinal cord. Results: P301S mice display regional microgliosis. Systemic LPS treatment induced exaggerated acute sickness behaviour and motor dysfunction in P301S mice compared with wild‐type controls and advanced the onset and accelerated chronic decline. LPS treatment was associated with increased tau pathology 24 hours after LPS injection and spinal cord microgliosis at the end stage. Discussion: This is the first demonstration that a single systemic inflammatory episode causes exaggerated acute functional impairments and accelerates the long‐term trajectory of functional decline associated with neurodegeneration in a mouse model of human tauopathy. The findings have relevance to management of human dementias. Highlights: P301S microgliosis is regional; activation occurs in the spinal cord but not in the cortex. Systemic LPS injection caused acute neurological deficits in P301S mice. This was associated with increased tau pathology 24 hours after LPS injection. This was independent of microglial priming as measured by IL‐1β hyperexpression. LPS injection advanced the onset of chronic decline in P301S mice.